Islamic Republic of Iran : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 2000)
The Islamic Republic of Iran inherited a highly centralized economy. The state-owned enterprises had monopolies over large sectors of the economy, including the financial system. This was compounded by Iran's excessive dependence on the volatile oil exports. Iran's five-year development plan aims at accelerating growth to create sufficient employment opportunities for a rapidly expanding labor force. De-monopolizing the economy, liberalizing trade, promoting private investment, strengthening the financial system, and improving the fiscal and monetary policy settings is required.